Neue koptische medizinische Rezepte - Richter, Tonio Sebastian (Zeitschrift für ägyptische Sprache und Altertumskunde, 2014)
The article presents four new additions to the inventory of Coptic medical texts. The papyrus fragments P.TT157-470 and P.Heid. G 698(c), both datable to the 4th/5th century CE, belong to the earliest known Coptic medical texts. One of the eye salves of P.TT157-470 and the type of eye salve called (kollyrion) monohemeron are otherwise attested in classical medical compendia, and the simple drugs of its materia medica are exclusively referred to by Greek loanwords, notably derived from genitive input forms. P.Louvre AF 12530, a 9 th /10 th -century papyrus strip, offers evidence for the subsequent replacement of Greek taxonomic vocabulary by Arabic terms, as well as for pharmaceutical concepts typical of Arabic medicine. Its scribe is identical to that of Bodleian MS Copt. (P) a.1; therefore, the Louvre medical and the Oxford alchemical recipes originally formed one medico-alchemical assemblage. Hitherto unpublished fragments of the miniature-sized parchment codex P.Carlsberg 500, whose central section was edited by Erichsen 1963, shed new light on the botanical systematics of this unique Coptic herbal.